Determinants of job performance of public servants in Asian countries: a systematic literature review - Ahmad Zahran, Siti Munirrah; Mohd Noor, Nurul Hidayana; Ghazali, Marni (Faculty of Administrative Science and Policy Studies, 2025)
The primary causes that affect job performance among civil servants in Asian countries were addressed in this systematic literature review. The review further determines six key themes that are based on 14 peer-reviewed studies published between 2020 and 2024, which are leadership styles and behaviours, emotional and psychological factors, organisational commitment and citizenship behaviour, human resource management practices and skills, organisational support and perceptions of fairness, and work environment and job demands. These factors play pivotal roles in improving job performance and are grounded in established frameworks such as Transformational and Servant Leadership Theory, Organizational Commitment Theory, and Strategic HRM, along with supporting concepts like Emotional Intelligence, Self-Efficacy, and Equity Theory. These perspectives elucidate the interaction of factors to shape performance outcomes. The cultural dynamics comprising collectivism and hierarchical structures affect how these factors are perceived as well as how it is applied across national contexts. It also emphasises the importance of people-centred leadership, fair governance, and culturally sensitive reforms that address workload pressures and psychological well-being in the public service. The limitations are indicating to the need for broader regional and longitudinal studies together with a narrow geographical scope and uneven thematic coverage, pointing to the need for broader regional and longitudinal studies.